The Effectiveness Of The Use Of Social Media In School Promotion At Ulul Albab Islamic Private Elementary School Jember - Dani Hermawan; Dindya Vikri Roemaissha (Aksara Shofa, 2025)
Currently, we are in an age with digital sundries, the use of the internet is not only in the business world but has touched the world of education. Such as SDS Islam Ulul Albab. Uniquely, this school since the beginning of its establishment has never printed banners to recruit new students. Those who aim to comb the group are busy working and do not have much free time. So the formulation of the problem is how effective the use of social media in school promotion at SDS Islam Ulul Albab Jember. Which aims to measure the effectiveness of the use of social media in school promotion at SDS Islam Ulul Albab Jember. The method used is sequential explanatory along with t-test analysis with the type of posttest-only control group design. With data collection techniques in the form of questionnaire distribution, interviews, observations, and documentation. The results of this study are that there is a significant effectiveness of the use of social media in school promotion conducted by SDS Islam Ulul Albab Jember proven based on the results of t count > t table (7,820 > 1,998340543), with a large percentage of effectiveness of 81%. This is supported by the existence of a special team responsible for managing social media called the media team. There are programs to develop the quality of educator resources and education personnel including supporting competency training such as editing training, recitation, PSDW, and the like.